2022
DOI: 10.3390/ijms231810558
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical Characterization of LTX-315 Anticancer Peptide Interactions with Model Membrane Platforms: Effect of Membrane Surface Charge

Abstract: LTX-315 is a clinical-stage, anticancer peptide therapeutic that disrupts cancer cell membranes. Existing mechanistic knowledge about LTX-315 has been obtained from cell-based biological assays, and there is an outstanding need to directly characterize the corresponding membrane-peptide interactions from a biophysical perspective. Herein, we investigated the membrane-disruptive properties of the LTX-315 peptide using three cell-membrane-mimicking membrane platforms on solid supports, namely the supported lipid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 88 publications
0
3
0
Order By: Relevance
“…This is the case with indolicidin, a peptide with reported antibacterial activity against a wide range of microorganisms and Gram-positive and Gram-negative bacteria (Ando et al 2010 ), with no secondary structure in solution or during interaction with membranes (Hsu & Yip 2007 ; Ladokhin et al 1999 ). Another recognized peptide LTX-315, known as Oncopore™, a synthetic oncolytic peptide active in several cancer cell lines, has also been shown to be structureless in aqueous solution and model membranes made of 100% PC, 70/30% PC/PS, and 50% v/v TFE by circular dichroism (Koo et al 2022 ). Our previous work with infrared spectroscopy also demonstrated the described outcome using tumoral and non-tumoral model membranes (Klaiss-Luna et al 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is the case with indolicidin, a peptide with reported antibacterial activity against a wide range of microorganisms and Gram-positive and Gram-negative bacteria (Ando et al 2010 ), with no secondary structure in solution or during interaction with membranes (Hsu & Yip 2007 ; Ladokhin et al 1999 ). Another recognized peptide LTX-315, known as Oncopore™, a synthetic oncolytic peptide active in several cancer cell lines, has also been shown to be structureless in aqueous solution and model membranes made of 100% PC, 70/30% PC/PS, and 50% v/v TFE by circular dichroism (Koo et al 2022 ). Our previous work with infrared spectroscopy also demonstrated the described outcome using tumoral and non-tumoral model membranes (Klaiss-Luna et al 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of action of daptomycin has been widely studied, and it has been demonstrated that, as a cyclic peptide, the structure does not present a helical or b-sheet structure (15,55). LTX-315, known as Oncopore TM , a synthetic oncolytic peptide active in several cancer cell lines, has also been shown to be structureless in aqueous solution and model membranes made of 100% PC, 70/30 % PC/PS, and 50% v/v TFE by circular dichroism (20). Our previous work with infrared spectroscopy also demonstrated the described outcome using tumoral and non-tumoral model membranes (19).…”
Section: Discussionmentioning
confidence: 99%
“…G m is directly proportional to the tendency of ions to flow through the tethered lipid bilayer, whereas C m is inversely related to membrane thickness [45][46][47]. The tBLM fabricated on the gold electrode was characterized using EIS to confirm its formation according to reference values [48,49], and the measured signals served as a baseline before 2000 µM compounds/mixtures were added to the tBLM platform for 30 min, which preceded a subsequent buffer washing step. Note that the baselines of G m and C m values for tBLM formation were in the acceptable range of <~3 µS and 0.7-1.2 µF/cm 2 , respectively.…”
Section: Eis Characterization Of Membrane-disruptive Interactionsmentioning
confidence: 99%